Concomitant percutaneous coronary intervention and transcatheter aortic valve replacement for aortic stenosis complicated with acute STEMI: a case report and literature review - Xu, Chengyi; Hu, Hanhua; Su, Xi (Frontiers in Cardiovascular Medicine, 2023)
Aortic stenosis (AS) complicated with acute ST-segment elevation myocardial infarction (STEMI) is a life-threatening emergency with high mortality. A 75-year-old male patient attended the emergency department of Wuhan Asia Heart Hospital in December 2021 with chest pain for 2 days and exacerbation for 1 h. The electrocardiogram (ECG) indicated atrial fibrillation with rapid ventricular response and ST-segment depression. Echocardiography showed severe AS and mild/moderate aortic insufficiency. The patient refused coronary angiography and further invasive procedures and then requested discharge, but he had recurrent chest pain on the third day. The ECG showed an extensive anterior wall STEMI. During preoperative preparation, he suffered from cardiogenic shock (CS). Concomitant percutaneous coronary intervention (PCI) and transcatheter aortic valve replacement (TAVR) was performed, but he died of CS and multiple organ failure 4 days after surgery. Patients with AS and STEMI might be susceptible to CS during perioperative period of concomitant PCI and TAVR, which requires proactive prevention.